Semaglutide Reduces Cardiomyocyte Damage Caused by High-Fat Through HSDL2 - Yang L; Pan X; Pan Z; Gao H; Ban J; Chen S (Dove Medical Press, 2024)
Lin Yang,1,2 Xiaoyu Pan,2 Zhenyu Pan,3 Haina Gao,4 Jiangli Ban,4 Shuchun Chen2,5,6 1Department of Internal Medicine, Hebei North University, Zhangjiakou, Hebei, People's Republic of China; 2Department of Endocrinology, Hebei General Hospital, Shijiazhuang, Hebei, People's Republic of China; 3Department of Internal Medicine, Shandong Medical College, Linyi, Shandong, People's Republic of China; 4Department of Endocrinology, The Second Hospital of Shijiazhuang, Shijiazhuang, Hebei, People's Republic of China; 5Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 6Hebei Key Laboratory of Metabolic Diseases, Hebei General Hospital, Shijiazhuang, Hebei, People's Republic of ChinaCorrespondence: Shuchun Chen, Department of Internal Medicine, Hebei Medical University, People's Republic of China, Tel +86 31185988406, Email chenshuc2014@163.comIntroduction: Obesity-induced inflammation and oxidative stress can cause damage to cardiomyocytes. Semaglutide has the potential to reduce glucose levels and weight, while hydroxysteroid dehydrogenase-like protein 2 (HSDL2) also plays a role in regulating lipid metabolism. This study aimed to investigate the expression of oxidative stress markers and HSDL2 in myocardium and serum under high-fat conditions, in order to elucidate the mechanism of obesity-induced myocardial injury and evaluate the impact of semaglutide on myocardial injury through HSDL2.Methods: Mouse models of obesity were established with semaglutide treatment. Palmitic acid-cultured mouse cardiomyocytes with HSDL2 knockout were used, as well as palmitic acid-induced high-fat environment models followed by semaglutide treatment. The levels of inflammatory and oxidative stress markers in serum and cardiomyocytes were measured. Additionally, the expression of HSDL2 and autophagy levels in different cell groups were assessed to evaluate the effect of semaglutide on high-fat diet-induced cardiomyocyte injury mediated by HSDL2.Results: Obesity increased oxidative stress, which was alleviated by intervention with semaglutide. Furthermore, semaglutide down-regulated HSDL2 expression in obese individuals. Moreover, palmitic acid-induced oxidative stress and autophagy were reduced when using cells with knocked out HSDL2 gene.Conclusion: These findings suggest that semaglutide may mitigate cardiomyocyte injury caused by a high-fat diet through regulation of HDLSDSLEP-1 expression. These discoveries are expected to unveil novel molecular mechanisms and provide new targets for clinical treatment.Keywords: obesity, inflammation, oxidative stress, semaglutide, HSDL2